Revolutionizing photovoltaic excellence: Unveiling a cutting-edge approach to assessing module enhancers for optimal area and cost efficiency - Sakhr M. Sultan; C.P. Tso; Raheem K. Ajeel; K. Sobayel; M.Z. Abdullah; K. Sopian; Ahmed Said Al Busaidi (Case Studies in Thermal Engineering, 2024)
A photovoltaic module (PV) functions as a device for producing electricity. Increasing the number of PV units leads to higher power generation, but this also requires a larger land's area. However, limitations in available space, especially on building rooftops, coupled with consumer demands for greater power output, pose a challenge. To tackle this issue, the PV enhancer technology has been introduced. It aims to boost power generation per unit area and has been evaluated in a previous study. While this existing approach effectively compares different PV enhancers, it becomes complex when considering both the PV and enhancer's area parameters. To simplify this, a novel method is introduced for the first time which incorporates a new correlation considering the area of both the PV and its enhancer, the combined net power generated, the PV's output power without an enhancer, and the maximum PV power under standard test conditions. It also includes the cost per watt of PV power and the manufacturing cost of the PV enhancer. The impact of each parameter on this new method is thoroughly explained. The proposed technique categorizes PV enhancers based on values derived from the new method. For instance, enhancers are classified as having maximum or minimum performance based on whether the value of the new method equals the minimum value of the area and cost-effectiveness factor or unity, respectively. The effectiveness of the new method is confirmed through testing on a real-world case from a previous experimental study, demonstrating its practicality. The new method has shown applicability in real world scenarios and can aid in categorizing types of PV enhancers, offering valuable insights for researchers, designers, and manufacturers for informed decision-making.